A produção de gênero textual de afásicos - Oliveira, ângela Aragão de (2008)
Aphasia is a disease that interferes directly in the communication of the individual, specially the in expressive one. In most cases, when the aphasic is in the process of (re) empowerment, is given more emphasis on the aspect of oral, leaving aside the writing. However, communication consists of two ways, and therefore it is interesting development work aimed also to write. It is noted that in some cases, the writing, is so poor as to oral and it is necessary to include it in the therapeutic process. Thus, the study of textual production, in written form, using the different genres textual, had intended to observe the changes that aphasia carries on writing of the subject affected by this pathology, in addition to providing a new therapeutic approach in the process of afásico. To do so, participated in this search 04 subject bearers of aphasia that are part of the Workshop on Writing Group's Convivência of the Catholic University of Pernambuco (UNICAP), which aims to address the issues and work related to the written language. The analysis of the qualitative data was, as this study is proposed to observe the production textual the aphasic before textual different genres, and so identify what kind textual more applicant and produced more easily by the bearer of aphasia. After analysis of the data collected has been that afásicos showed ease in producing textual genres linked to concrete situations, as opposed to production of the genera needing achieve a relationship with abstract situations. Thus, it is important that fonoaudiólogos, admit a posture functional instead of organicista, enabling the distancing of tests, focusing uses descontextualizados of language, which exclude the heterogeneous and subjective aspects of the language. Therefore, the (re) Empowerment of aphasia should allow the afásicos use practices of writing that only the written genres can provide, since this attitude shows itself as a path for the fruitful work therapeutic fonoaudiológico